Visual impairment and blindness in rural central India: the Central India Eye and Medical Study. (8th June 2012) - Nangia, Vinay; Jonas, Jost B.; Gupta, Rajesh; Khare, Anshu; Sinha, Ajit
Abstract: Purpose: The aim of the study was to investigate prevalence of visual impairment in rural central India. Methods: The population‐based Central India Eye and Medical Study included 4711 subjects with an age of 30+ years. Presenting visual acuity (PRVA) and best‐corrected visual acuity (BCVA) were recorded. Visual impairment and blindness were defined using the World Health Organization (WHO) standard and United States (US) standard. Results: On the basis of PRVA and using WHO and US standards, 1049 [22%; 95% confidence interval (CI): 21.1, 23.5] subjects and 1290 (27%; 95% CI: 26.1, 28.7) subjects, respectively, were visually impaired, and 35 (0.7%; 95% CI: 0.5, 1.0) subjects and 116 (2.5%; 95% CI: 2.0, 2.9) subjects, respectively, were blind. The corresponding age‐standardized prevalence figures were 17%, 21%, 0.5% and 2%, respectively. Using best‐correcting glasses could eliminate PRVA‐visual impairment/blindness in 729 subjects (67% of all subjects with visual impairment/blindness). On the basis of BCVA and using WHO and US standards, 333 (7%; 95% CI: 6.3, 7.8) subjects and 473 (10%; 95% CI: 9.2, 10.9) subjects, respectively, had visual impairment, and 22 (0.5%; 95% CI: 0.3, 0.7) and 31 (0.7%; 95% CI: 0.4, 0.9) subjects, respectively, were blind. Corresponding age‐standardized prevalence figures were 5%, 8%, 0.4% and 0.5%, respectively. Causes for BCVA‐visual impairment/blindness were cataract (75%), postoperative posterior capsular opacification (4%), surgical complications (2%), corneal opacifications (2%), age‐related macular degeneration (2%), other macular diseases (1%), and glaucoma (1%). Conclusions: Age‐standardized prevalence of PRVA‐visual impairment/blindness (WHO definition) in the adult population of rural central India was 17%. Most frequent cause was undercorrected refractive error. Supply of correct glasses is the most efficient way to improve vision in the rural central India.